The contribution of syntactic–semantic approach to the search for complementary literatures for scientific or technical discovery - Vicente-Gomila, Jose M. (Scientometrics, 2014)
The present paper tries to show that the current state of the art in syntactics and semantics, in computer systems based on the theory of inventive problem solving known as TRIZ, may help in the task of literature based discovery. With a structured and logic cause linkage between concepts, LBD could be faster and with less expert involvement at the beginning of the LBD process. The author tries to demonstrate the concept with two different problems: the hearing and balance problem known as Meniere’s disease, and to some of the current problems in the lithium air batteries for electric vehicles. By using open literature based discovery from An to Bn and from Bn to Cn, and with the logic relationships of real causes and effects approach, the author finds several relative new concepts such as vitamin A. Other concepts as niacin or fish oil, are also found, as potential to help in the Meniere’s disease. Secondly, using such procedure the author is able to find patents from disparate domain of expertise, as patents about odor control or metal casting .